Common injuries among Brazilian Jiu Jitsu practitioners in Medan City - Lazuardi, Maulana Umar; Edlin, Edlin; Mukti, Ade Indra; Napitu, Sabar Hamonangan Victoranius; Setiawan, Deni (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Brazilian Jiu Jitsu (BJJ) is a martial art that focuses on floor fighting and was first popularized in Brazil. The BJJ originally focused on entertainment, health, and self-development. These goals changed when practitioners began participating in competitions in which there was a significant increase in the number of BJJ injuries. A pre-survey in the field indicated that many jiu jitsu practitioners were affected by common injuries. The type of research in this study is a descriptive survey with a cross-sectional approach conducted at Ryu Dojo Martial Arts Center, Musi Jiu Jitsu, and PBJI Medan City in March 2024. Data were collected in the form of questionnaires, interviews, and medical records of practitioners diagnosed with injuries who were sampled. Univariate analysis was used to obtain the frequency distribution of respondents for each variable, namely age, gender, belt level, weight, training frequency, and competitor status. The results of the study were analyzed using SPSS version 27.0. The results showed that the highest number of practitioners was in the late teenage group (53.8%), the highest gender was male (92.3%), and the highest number of practitioners was white belt (69.2%). Based on body weight, the highest number of practitioners was in the Light Feather category (< 64 kg/141 lbs) with a percentage of 26.9%, and the most training hours were 3-5 hours 16 (30.8%). Lower Back Pain was the most common injury with a total of 25 practitioners. A total of 75% of the practitioners stated that their daily activities were disrupted because of their injuries. It can be concluded that the majority of BJJ participants were in their late teens, male was the most common gender, and white belts were the most common practitioners. The most common injury was lower back pain due to the amateur competitor status. Most respondents stated that their injuries interfered with their daily activities.